Mechanochemical Synthesis of Diarylethynes from Aryl Iodides and CaC2 - van Bonn, Pit; Bolm, Carsten (Synlett, 2022)
A mechanochemical synthesis of diarylethynes from aryl iodides and calcium carbide as acetylene source is reported. The reaction is catalyzed by a palladium catalyst in the presence of copper salt, base, and ethanol as liquid assisting grinding (LAG) additive. Various aryl and heteroaryl iodides have been converted in up to excellent yields.
Keywords: mechanochemistry; calcium carbide; ball milling; diarylethyne; catalysis; palladium